Determination of level of physical preparedness of future engineers of railway transport. - Yefremova A.Y (Kharkov National Pedagogical University, 2012)
Directions of increase of level of physical preparedness of student young people are considered. 48 students took part in research. The level of physical preparedness of students on the indexes of speeding up, co-ordination, flexibility and force was determined. Professional duties are certain and requirement to physical and psychological physical preparation of specialists to the controller-operator groups of railway transport. Directions of maintenance of health of student young people and improvement of level of its general physical preparedness are offered in the process of employments. It is shown that progress and productivity of future professional activity of students depends on the state of health, psychological firmness, capacities for a concentration and switching of attention, possibilities to work in emotional nervous tension at the deficit of time. Directions optimization of process of physical preparation of students are shown, development of physical qualities.